The impact of Covid-19 on coverage of children with required vaccines in the Republic of Serbia - Zlatanović, Milena; Krstić, Bojana; Despotović, Milena; Krstić, Miloš; Milovanović, Marija (PONS - medicinski časopis, 2023)
Introduction: Infectious diseases have always been a challenge for medicine and healthcare workers. In addition to the enormous progress of medicine, they still represent a major public health problem. The pandemic caused by Covid 19 shows that. Due to the pandemic itself, the overload of the health care system, the fear of infection, the reallocation of health resources to respond to the pandemic, and other measures to control and suppress the infection, routine immunization services for children have been disrupted around the world.The aim of the work is to examine the impact of Covid-19 on the frequency of immunization of children with mandatory vaccines.Method of work: Through retrospective analysis of data from the annual reports of the WHO and the Institute for Public Health of the Republic of Serbia "Dr. Milan Jovanović Batut", comparative data on coverage of required vaccination against infectious diseases in the Republic of Serbia was provided. Research results: The results of a five-year analysis in the Republic of Serbia indicate that coverage of more than 95% was met only with immunization against tuberculosis, while against diphtheria, tetanus and whooping cough, coverage of 95% was until 2019, only to record a decline later. In 2021, a percentage decrease can be seen for all vaccines except the tuberculosis vaccine, and the lowest coverage is for the MMR vaccine (74.8%). In Serbia, in 2020 compared to 2019, the percentage of people vaccinated with the MMR vaccine decreased by 9.9%, i.e. by 3.3% in 2021 compared to 2020, and the data for central Serbia show a decrease of 11.6% in time period from 2019 to 2021.Conclusion: The trend of decline in immunization coverage of mandatory vaccines in Serbia follows the global trend, with the exception of the MMR vaccine, where a significantly greater decline is recorded in Serbia.Key words: Covid 19, Pandemic, Compulsory vaccination, Vaccine preventable diseases, Vaccination coverage